Marine fungi as a goldmine for novel antibiotics: a 2024 perspective - Pan, Chengqian; Hassan, Syed Shams ul; Muhammad, Ishaq; Jin, Huizi (Frontiers in Marine Science, 2025)
The microbial diversity in oceans is considerable, widely distributed in seawater, marine sediments, and marine organisms. Compared with terrestrial resources in traditional natural product research, the living environments of marine microorganisms are starkly different. The drastic differences in survival conditions, such as high salinity, oligotrophic conditions, lack of light, and limited oxygen, determine that microorganisms exhibit distinctive characteristics in metabolism, survival modes, and adaptive mechanisms. These factors contribute to significant distinctions in secondary metabolic pathways and enzymatic reaction mechanisms between marine and terrestrial microorganisms. In this review, we summarized a total of 72 novel natural products with antibacterial activity, published in 2024, which are derived from marine-derived fungi. These products (polyketides, alkaloids, terpenoids, and peptides) are emphasized in terms of their structures and biological activities. This article aims to provide useful information for the research and development of novel antibiotics.